The God in Me: Faith, Reality TV, and Black Women - Egwu, Chetachi A. (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The display of spirituality, faith and religion is not a new phenomenon among black women in the United States, nor is it new to the world of media. Africans came to the Americas with their own sense of spirituality and religion, and the awareness of a higher being became the mortar that bound the community together during the trials of enslavement and subsequent oppression. Not surprisingly, this legacy of worship continues to provide solace and strength, with black women at the helm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

High Tea, Church Hats, Pastor Wives, and Friendships: A Critical Race Feminism Analysis of Black Women in Preachers of L.A. - Whittington Cooper, Elizabeth (Black Women's Portrayals on Reality Television: The New Sapphire, 2016)
The premise of the show revolves around six preachers in the Los Angeles area. They each pastor churches ranging from 3,500– 4,000 members; however, one pastor’s church has nearly 20,000 members (season 1: episode 1). A multitude of cameras follow the stories of each of the pastors’ lives, their relationships with each other, as well as their wives relationships with one another. The show has five black male preachers and one white male preacher. In season 1, all of the pastors— except for two— are married; one of the unmarried pastors is engaged to the mother of his child, and the other has a long-standing relationship with a female friend who frequently appears on the show. As viewers watch the show, they are given a glimpse into the world of evangelical preachers. Although at first glance the show seems to only focus on the men, the women provide an interesting glimpse at what it means to be a preacher’s wife, fiancée, or female companion. There were a total of eight episodes that aired over the course of two months. This chapter explores how black women and their friendships are portrayed on Preachers of L.A. — including the one white woman on the show. It also examines their discourse between one another— using critical race feminism to analyze the roles of these women as first ladies (a term used to describe the wives of pastors), their relationship with one other, and the conversations they have surrounding sex, marriage, relationships, and friendships. The chapter focuses on the first season of the show, which began in the fall of 2013. The show was later renewed for a second season, which began airing late summer 2014. This critique attempts to bring awareness to black women in the church and the discourse that perpetuates the stereotypes of black women on television. It also aims to initiate further conversations on various stereotypes— regardless of context— that have the potential to bear negatively on black women.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Down in the Treme … Buck Jumping and Having Fun?: th Impact of Depictions of Post-Katrina New Orleans on Viewers’ Perceptions of the City - LeDuff, Kim M. (Watching While Black, 2012)
Five years after Hurricane Katrina devastated New Orleans, Louisiana, life remained not normal still for many residents of the city. And while mainstream news organizations remembered the fifth anniversary of the hurricane with extensive coverage, it was the work of filmmaker Spike Lee and television program creators David Simon and Eric Overmyer that perhaps created the greatest buzz about the fifth anniversary of Katrina in 2010. Spike Lee’s first documentary, When the Levees Broke , was released in 2006. It documented what happened in New Orleans through the voices of local residents, politicians, and experts during and immediately after the storm.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Pratiques professionnelles en arts visuels issues de l'autochtonie et de la diversité à Montréal - Uzel, Jean-Philippe; Conseil des arts de Montréal (2017)
Rapport commandé par le Conseil des arts de Montréal
OCLC: 1081308169
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Sensible Objects: Colonialism, Museums, and Material Culture - Edwards, Elizabeth; Gosden, Chris; Phillips, Ruth B. (Routledge, Taylor & Francis Group, 2020)
Anthropologists of the senses have long argued that cultures differ in their sensory registers. This groundbreaking volume applies this idea to material culture and the social practices that endow objects with meanings in both colonial and postcolonial relationships. It challenges the privileged position of the sense of vision in the analysis of material culture. Contributors argue that vision can only be understood in relation to the other senses. In this they present another challenge to the assumed western five-sense model, and show how our understanding of material culture in both historical and contemporary contexts might be reconfigured if we consider the role of smell, taste, touch and sound, as well as sight, in making meanings about objects.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Critics and the Slippery Terrain of Latinx Art - Dávila, Arlene (Latin American and Latinx Visual Culture, 2019)
When E. Carmen Ramos organized Our America: The Latino Presence in American Art (2013) at the Smithsonian American Art Museum in Washington, DC, art holdings of Latinx artists at the institution were minimal and unbalanced. The museum lacked works by foundational figures; entire groups like Dominican Americans were missing, as were genres like abstract art; and with a collection dominated by colonial and folk art and work by Mexican Americans, it was impossible to produce any comprehensive exhibition of contemporary Latinx art, much less one that represented the diversity of artists and trends. Ramos was one of the few Latinx curators hired in the aftermath of the infamous 1994 “Willful Neglect” report documenting a historical pattern of discrimination at the Smithsonian Institute and calling for the hiring of Latinx curators to help direct the Smithsonian’s priorities in research, collections, and exhibitions.1 Twenty-five years later, this pattern of exclusion continues apace. In 2018, a study by UCLA’s Chicano Studies Research Center found that while the Smithsonian’s Latinx workforce grew from 2.5 percent to 10.1 percent, this growth falls short of representing the growth of the Latinx population, which since 1994 has doubled to 17.8 percent of the total population. In sum, the task of putting a dent in a mostly white canonical art history and collection was a daunting one, and whatever Ramos did would be a politically charged intervention. This would be the first major scholarly survey exhibition of Latinx art, a statement to insert it as central to US art history, and the first major show of its type in a major North American museum in decades.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Metamorphic and Sensuous Brown Bodies: Queer Latina/x Visual and Performance Cultures in San Francisco Strip Clubs, 1960s–1970s - Otálvaro-Hormillosa, Gigi (Latin American and Latinx Visual Culture, 2019)
In the 1960s, topless entertainment became legal in San Francisco, although cross-dressing continued to be criminalized. This article documents queer Latina/x visual and performance cultures of San Francisco’s strip club industry during this critical moment. It employs visual and performance analyses that draw from ethnographic interviews and archival research about three Latinas who performed as exotic dancers during this period, two of whom were out transsexuals: Roxanne Lorraine Alegria, Vicki Starr, and Lola Raquel. Engaging Marcia Ochoa’s notion of “spectacular femininities” and Juana María Rodríguez’s theory of “queer gesture,” the article maps out a queer Latina/x herstoriography about the early days of topless entertainment in San Francisco. It demonstrates how the transgressive practices of these Latina performers enrich genealogies of queer and Latina/x performance and visual cultures since the 1960s. It thus contributes to the expansion and intersection of the fields of performance studies, Latina/x studies, and feminist, gender, and sexuality studies. These fields and their intertwinings offer critical tools to resist the sexism, homophobia, racism, transphobia, and whorephobia that pervade every level of society, as well as the cultural amnesia to which San Francisco has been increasingly prone due to its incessant gentrification and growing technocracy since the early 2010s.RESUMEN Este artículo documenta las culturas visuales y de performance latinas/x queer de los clubes de striptease de San Francisco durante un momento crítico en la historia de la ciudad. En la década de 1960, los shows en topless se legalizaron en San Francisco, aunque el travestismo se continuó criminalizando. Otálvaro-Hormillosa emplea análisis visuales y de performance que se basan en entrevistas etnográficas e investigación de archivo sobre tres latinas que actuaron como bailarinas exóticas durante este período, dos de las cuales reconocían públicamente que eran transexuales: Roxanne Lorraine Alegria, Vicki Starr y Lola Raquel. En diálogo con la noción de “feminidades espectaculares” de Marcia Ochoa y la teoría de “gestos queer” de Juana María Rodríguez, Otálvaro-Hormillosa describe una historiografía latina/x queer propiamente femenina sobre los primeros días del entretenimiento en topless en San Francisco. El artículo demuestra cómo las prácticas transgresoras de estas intérpretes latinas enriquecen las genealogías de las culturas visuales y de performance queer y latinas/x desde los años sesenta. Al hacerlo, contribuye a la expansión e intersección de los campos de los estudios de performance, estudios latinas/x, y estudios feministas, de género y de sexualidad. Estos campos y sus entrecruzamientos pueden ofrecer herramientas críticas para resistir el sexismo, la homofobia, el racismo, la transfobia y la putafobia que permea todos los niveles de la sociedad, así como la amnesia cultural a la que San Francisco ha sido cada vez más propenso debido a su incesante gentrificación y creciente tecnocracia desde principios de los años 2010.RESUMO Este artigo documenta a cultura visual e de performance na indústria de clubes de strip-tease de São Francisco, durante um momento crítico da história da cidade. Nos anos 60, o entretenimento topless se tornou legal em São Francisco, embora a prática do cross-dressing continuasse criminalizada. Otálvaro-Hormillosa emprega análise visual e de performance baseadas em entrevistas etnográficas e pesquisas de arquivos sobre três latinas que se apresentaram como dançarinas exóticas durante esse período, duas das quais eram transexuais: Roxanne Lorraine Alegria, Vicki Starr e Lola Raquel. Engajando a noção de “feminilidades espetaculares” de Marcia Ochoa e a teoria do “gesto queer” de Juana María Rodríguez, Otálvaro-Hormillosa mapeia uma herstoriografia queer latina/x sobre os sobre os primórdios do entretenimento topless em São Francisco. O artigo demonstra como as práticas transgressivas dessas artistas latinas enriquecem as genealogias das culturas visual e de performance queer e latina/x desde os anos 1960. Deste modo, contribui para a expansão e intersecção dos campos de estudos da performance, estudos latinos e estudos feministas, de gênero e sexualidade. Esses campos e seus entrelaçamentos podem oferecer ferramentas críticas para resistir ao sexismo, homofobia, racismo, transfobia e putafobia que permeiam todos os níveis da sociedade, bem como a amnésia cultural para a qual San Francisco tem sido cada vez mais propensa devido à sua gentrificação incessante e crescente tecnocracia desde o início dos anos 2010.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."–(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

African American Art and Artists - Lewis, Samella (University of California Press, 2003)
Samella Lewis has brought African American Art and Artists fully up to date in this revised and expanded edition. The book now looks at the works and lives of artists from the eighteenth century to the present, including new work in traditional media as well as in installation art, mixed media, and digital/computer art. Generously and handsomely illustrated, the book continues to reveal the rich legacy of work by African American artists.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Making Race : Modernism and Racial Art in America - Francis, Jacqueline (University of Washintong Press, 2012)
A history of a past phenomenon - racial art - which has ramifications for the present.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé